AKUNTANSI REKSADANA PRINSIP STANDAR AKUNTANSI KEUANGAN (PSAK) NO. 49 - Arna Suryani (Universitas Batanghari Jambi, 2009)
Mutual fund can be interpreted as place of fund accumulator from public as investor by fund manajer then inculcated at investment portofolio. Investment portofolio is allocation leg asset like stock, bond, other money market or securities. The analysis use descriptive analysis to see how accounting treatment arranging special deal related to mutual fund. Investment in mutual fund has high risk on that account evaluation portofolio having high liquidity before invests in. Accounting treatment specially PSAK number 49 to mutual fund can give assurance and trust of client to mutual fund Key Words : Invesment, Financial Asset, Mutual fund, Portofolio